The Effectiveness of Cirebon Siaga 112 Services in Handling Disaster Emergencies in Cirebon City - Nabiilah Khoirunnisaa; Hery Nariyah (CV. Media Digital Publikasi Indonesia, 2026)
This study discusses the Cirebon Siaga 112 service which aims to make it easier for the public to report emergency situations, one of which is a disaster emergency. The Cirebon Siaga 112 service still has several obstacles, including the number of prank calls, uneven socialization, and network disruption from providers. The purpose of this study is to examine the effectiveness of the Cirebon Siaga 112 service and to find out the supporting factors and factors inhibiting the effectiveness of the program in its implementation. This research was conducted using qualitative research methods through interviews, literature studies, and documentation studies. This study uses the theory of program effectiveness according to Budiani in Mutiarin & Khadafi [1] with four indicators: target accuracy, program socialization, program objectives, and program monitoring. The results of the study show that the Cirebon Siaga 112 Service has not been running effectively. A strategy to strengthen socialization to the community and improve network infrastructure is needed so that the Cirebon Siaga 112 service can run effectively.